MOBILE PHONE APPLICATION DEVELOPMENT FOR INTERROGATING EXTERNAL SENSOR - Ag Tahir, Ag Shahrin Afwan (Universiti Teknologi Petronas, 2011)
Recently, Smartphone processing power shows a remarkable performance on doing multitask function set by the user. As the manufacturing industry has come to a further development on data inspection by such sensor for example; Temperature Sensor, Pressure Sensor, Level Sensor, etc, both task of acquiring and analyzing data will need to be carried out at different time. By utilizing mobile phone as the main target data acquisition, data are easily access at the end of the user finger tips. Literature review comprises all the keywords and terms that we need to know before we can proceed to the system development. The methodology focus on more on project flow, hardware and software used such as, Programmable Integrated Circuit (PIC) Microcontroller, Bluetooth Module, Lithium Polymer Battery, 02 XDA Mobile Phone, vxHpc Software, Windows Visual Studio 2008, MPLAB 8.10 and etc. As for the result, the external system already able to communicate and interconnect with mobile phone with the ability of vxHpc software to act as hyper terminal for mobile phone. The external device are attached with internal temperature sensor (LM35DZ) and able to be connected with 3 external sensors as the users are able to interrogate the whole system by giving command and getting specific sensor data from external sensor device. As for conclusion, the system can be already be used for specific application as the micro controller are already comprises eighty percent of its entire program memory utilization.